THE IMPLEMENTATION OF INTERDISCIPLINARY APPROACH TO WRITING 1 SUBJECT FOR STUDENTS OF ENGLISH DEPARTMENT - Simanjuntak, Tiur; Sari, Evi Agustina; Gustiani, Sri; Yusri, Yusri (Orbith, 2018)
This study focuses on integrating subjects in the area of hospitality industry with Writing 1 for students of English Department at higher Technical Vocational Education Training (TVET). The integrating is necessary because language is taught for contextual communication not for the sake of the language itself. The objective of this study is to combine hospitality industry subjects such as House Keeping, Hotel Management, with the purpose of Writing 1 and it is called interdisciplinary learning. To reach the objective, mix method is used. Qualitative method is used and it is supported by quantitative one. Several factors are involved in this study. They are curriculum, teachers of hospitality subjects, English teachers, Students of English Department, and the competency expected from Writing 1. The result shows that high engagement is required to make interdisciplinary learning work. Several subjects in hospitality industries are identified to be integrated in Writing 1 including Guiding Technique, Profession Ethics, Tourism Marketing, Hygiene and Sanitation, Hotel Management, Tourism Destination and Attraction. The contentof those subjects are simplified according to the objective of Writing 1 for higher TVET. Keywords: Interdisciplinary Approach, Writing, English Teaching, Hospitality Industry